2019
DOI: 10.1002/j.2617-1619.2019.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

MuRF1 and MuRF2 are key players in skeletal muscle regeneration involving myogenic deficit and deregulation of the chromatin‐remodeling complex

Abstract: Background Skeletal muscle regeneration is a powerful and highly synchronized process and it is well described that intracellular pathways related to anabolic responses are readily activated. On the other hand, the role of catabolic pathways in the skeletal muscle regenerative response is much less understood. In the present study, we hypothesized that MuRF1, a key gene involved in skeletal muscle mass loss, and its close counterpart MuRF2 play a role in skeletal muscle regeneration. Methods and results Wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
0
9
2
2
Order By: Relevance
“…Interestingly, a subsequent study (33) showed that MuRF2 and MuRF3 deletion in mice causes severe skeletal muscle histological alterations, including sarcomeric disarrays, reinforcing the notion that MuRF2 can be involved in cytoskeleton organization. More recently, MuRF2 was also shown to be a skeletal muscle tissue organizer in mice with MuRF1 and MuRF2 deletion (21). In spite of these data clearly establishing a connection between MuRF2 and the skeletal muscle fiber cytoskeleton, no studies had so far approached fibroblasts, which are cells extremely dependent upon their cytoskeleton to function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a subsequent study (33) showed that MuRF2 and MuRF3 deletion in mice causes severe skeletal muscle histological alterations, including sarcomeric disarrays, reinforcing the notion that MuRF2 can be involved in cytoskeleton organization. More recently, MuRF2 was also shown to be a skeletal muscle tissue organizer in mice with MuRF1 and MuRF2 deletion (21). In spite of these data clearly establishing a connection between MuRF2 and the skeletal muscle fiber cytoskeleton, no studies had so far approached fibroblasts, which are cells extremely dependent upon their cytoskeleton to function.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were isolated from the hind limb muscles of male FVB mice (∼8 weeks old, 30±3 g). Cell isolation and digestion were made as previously described (20,21). After digestion, the cells were incubated at 37°C in an atmosphere of 5% CO 2 for 40-50 min on 75 cm 2 tissue culture dishes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies buttress the view that increased FoxO signalling and the activation of the transcription factors nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB), MuRF1, and muscle atrophy F‐box (MAFbx) in skeletal muscle play major roles during cachexia onset and progression . MuRF1 and MAFbx are essentially involved in muscle atrophy development.…”
Section: Basic Sciencementioning
confidence: 99%
“…A proteína MuRF1 em conjunto com a sua homóloga MuRF2, além de desempenharem um papel na atrofia muscular, também são importantes na formação do sarcômero e diferenciação miogênica (McElhinny et al, 2004). Nosso grupo de pesquisa demonstrou que a ablação destes MuRFs prejudica a diferenciação das células satélites, levando a um déficit no processo de regeneração muscular em camundongos (Moriscot et al, 2019), demonstrando assim que MuRFs também desempenham um papel importante na regulação da regeneração muscular esquelética.…”
Section: Regeneração Muscular Esqueléticaunclassified